A multilayer composite oxide coating on a nickel substrate surface and a method for producing the same
Patent Information
- Application Number
- CN202611107063.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-09-22
- Estimated Expiration
- 2046-07-24
AI Technical Summary
[0005]本发明的主要目的是提供一种在镍基材表面制备多层复合涂层的方法,针对现有钌基涂层存在的组元易流失、涂层与基体结合力弱、抗热冲击能力差的缺陷
钌基混合氧化物中间层中多种组元形成协同效应,配合薄铂过渡层强化界面结合,使涂层在严苛工况下仍能保持优异的化学稳定性和层间结合强度。
Smart Images

Figure CN122610056B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal surface coating technology, and in particular to a multilayer composite oxide coating on a nickel substrate and its preparation method. Background Technology
[0002] Nickel and its alloys are widely used in chemical, aerospace, and marine industries due to their good machinability and corrosion resistance. Functional oxide coatings are often prepared on their surfaces to improve their resistance to high-temperature oxidation and corrosion. The coating thermal decomposition method has become a common method for preparing such coatings due to its advantages such as simple process and adjustable composition.
[0003] However, the following common technical challenges still exist when using this method to prepare multilayer oxide coatings on nickel substrates: First, the coating and the nickel substrate have a large difference in thermal expansion coefficients, resulting in weak adhesion and easy cracking and peeling under thermal cycling conditions; second, the interfacial compatibility between multilayer coatings is poor, and the accumulation of internal stress leads to microcracks and structural instability; third, the functional oxide layer is inherently brittle, and its components are easily lost under harsh environments, resulting in continuous performance degradation; fourth, traditional outer protective layers are either not dense enough or have poor conductivity, making it difficult to effectively buffer the coupled impact of multiple factors.
[0004] Therefore, there is an urgent need to develop a method for preparing multilayer composite coatings that can systematically solve the problems of adhesion, interlayer matching, phase stability and surface protection of oxide coatings on nickel substrates. Summary of the Invention
[0005] The main objective of this invention is to provide a method for preparing a multilayer composite coating on a nickel substrate, addressing the shortcomings of existing ruthenium-based coatings, such as easy loss of components, weak adhesion between the coating and the substrate, and poor thermal shock resistance.
[0006] To address the aforementioned deficiencies, this invention provides a method for preparing a multilayer composite oxide coating on a nickel substrate, comprising the following steps: The surface of the nickel substrate is roughened by sandblasting, and then cleaned with organic solvent, immersed in acid solution and immersed in alkaline solution in sequence to obtain the pretreated nickel substrate. The pretreated nickel substrate is heated and kept warm in an oxygen-containing atmosphere to generate an in-situ nickel oxide underlayer on the surface of the nickel substrate. A solution containing a platinum precursor is coated onto the nickel oxide substrate, dried, and then thermally decomposed. The coating, drying, and thermal decomposition processes are repeated until a preset loading amount is reached to form a thin platinum transition layer. A mixed solution containing ruthenium precursor, platinum precursor and neodymium precursor is coated on the thin platinum transition layer. After drying, it is subjected to thermal decomposition treatment. The coating, drying and thermal decomposition operations are repeated until a preset loading amount is reached to form a ruthenium-based mixed oxide intermediate layer. A mixed solution containing platinum precursor and cerium precursor is coated on the intermediate layer of the ruthenium-based mixed oxide. After drying, it is subjected to thermal decomposition treatment. The coating, drying and thermal decomposition operations are repeated until a preset load is reached to form a platinum-cerium mixed oxide protective layer. The nickel substrate with all coatings completed is placed in an oxygen-containing atmosphere for annealing to obtain a multilayer composite coated nickel substrate.
[0007] Furthermore, the step of coating the nickel oxide substrate with a solution containing a platinum precursor, drying it, and then subjecting it to thermal decomposition, repeating the coating, drying, and thermal decomposition operations until a preset loading amount is reached to form a thin platinum transition layer, includes: Chloroplatinic acid was dissolved in a solvent in which isopropanol and deionized water were mixed in a volume ratio of 1:1. Hydrochloric acid solution was added to adjust the acidity, and a platinum precursor solution with a total platinum concentration of 80-120 g / L was prepared. The platinum precursor solution is uniformly coated on the surface of the nickel oxide substrate and dried at 110℃-130℃ for 5-15 minutes, allowing the solvent to slowly evaporate and forming a precursor film on the substrate surface. The dried substrate is placed in an oxygen-containing atmosphere and kept at 480℃-520℃ for 15-25 minutes for thermal decomposition treatment, so that the platinum precursor is fully decomposed and transformed, and forms an interface bond with the underlying nickel oxide substrate. Repeat the above coating, drying and thermal decomposition operations 2-4 times until the platinum loading reaches 1.0-2.0 g / m², forming a continuous thin platinum transition layer.
[0008] Further, the step of dissolving chloroplatinic acid in a solvent of isopropanol and deionized water in a 1:1 volume ratio, adding hydrochloric acid solution to adjust the acidity, and preparing a platinum precursor solution with a total platinum concentration of 80-120 g / L includes: Add chloroplatinic acid to a solvent in which isopropanol and deionized water are mixed in a volume ratio of 1:1, and stir until completely dissolved; Hydrochloric acid solution was added dropwise while stirring to adjust the acidity of the solution to a concentration of 0.05 mol / L to 0.2 mol / L. Stirring was continued until the solution became clear and transparent to obtain the platinum precursor solution.
[0009] Furthermore, the step of coating the thin platinum transition layer with a mixed solution containing ruthenium precursor, platinum precursor and neodymium precursor, drying and then thermally decomposing it, repeating the coating, drying and thermal decomposition operations until a preset loading amount is reached to form a ruthenium-based mixed oxide intermediate layer, includes: Ruthenium chloride, chloroplatinic acid, and neodymium nitrate are dissolved in a mixed solvent of isopropanol and deionized water at a molar ratio of ruthenium, platinum, and neodymium of (70-85):(5-15):(10-20) to prepare a coating solution. The mass concentration of the coating solution, based on the total metal content, is 150 g / L-250 g / L. The coating liquid is brushed onto the surface of the thin platinum transition layer, dried at 100℃-140℃ for 5-15 minutes, and then thermally decomposed at 480℃-520℃ in an oxygen-containing atmosphere for 15-30 minutes. Repeat the brushing, drying and thermal decomposition process 5 to 7 times until the total metal loading in the ruthenium-based mixed oxide intermediate layer reaches 5.0 g / m² to 8.0 g / m².
[0010] Furthermore, the step of coating the ruthenium-based mixed oxide intermediate layer with a mixed solution containing platinum and cerium precursors, drying it, and then subjecting it to thermal decomposition, repeating the coating, drying, and thermal decomposition operations until a preset loading amount is reached to form a platinum-cerium mixed oxide protective layer, includes: Chloroplatinic acid and cerium nitrate were dissolved in a mixed solvent of isopropanol and deionized water at a platinum to cerium molar ratio of 30:70-40:60 to prepare a coating solution. The mass concentration of the coating solution, based on the total metal content, was 80 g / L-120 g / L. The coating solution is brushed onto the surface of the ruthenium-based mixed oxide intermediate layer and dried at 100℃-140℃ for 5-15 minutes, followed by thermal decomposition at 430℃-490℃ in an oxygen-containing atmosphere for 10-20 minutes. Repeat the brushing, drying, and thermal decomposition process 2 to 4 times until the total metal loading of the protective layer reaches 1.0 g / m² to 3.0 g / m², forming a continuous platinum-cerium mixed oxide protective layer.
[0011] Furthermore, the step of placing the pretreated nickel substrate in an oxygen-containing atmosphere for heating and heat preservation to generate a nickel oxide underlayer in situ on the surface of the nickel substrate includes: The pretreated nickel substrate is placed in an oxygen-containing atmosphere and heated to 480℃-520℃ and held for 40-60 minutes. After the heat preservation is completed, heating is stopped, and the nickel substrate cools with the furnace, forming a continuous nickel oxide underlayer that is metallurgically bonded to the substrate on the surface.
[0012] Furthermore, the step of annealing the nickel substrate with all coatings completed in an oxygen-containing atmosphere to obtain a multilayer composite coated product of nickel substrate includes: A nickel substrate having a nickel oxide underlayer, a thin platinum transition layer, a ruthenium-based mixed oxide intermediate layer and a platinum-cerium mixed oxide protective layer formed sequentially is placed in an oxygen-containing atmosphere and heated to 480℃-520℃ and held for 20-40 minutes. After the heat preservation is completed, heating is stopped, and the nickel substrate is cooled with the furnace to eliminate internal stress in the coating and stabilize the interfacial bonding between the coatings, thus obtaining a multi-layer composite coating product with a nickel substrate.
[0013] The present invention also provides a multilayer composite coating product on a nickel substrate surface with a multilayer composite coating, which is prepared by the above-described method for preparing a multilayer composite oxide coating on a nickel substrate surface.
[0014] Furthermore, the multilayer composite coating product on the nickel substrate surface includes a nickel substrate, and the surface of the nickel substrate is provided with a nickel oxide underlayer, a thin platinum transition layer, a ruthenium-based mixed oxide intermediate layer and a platinum-cerium mixed oxide protective layer from the inside to the outside. The platinum loading of the thin platinum transition layer is 1.0 g / m²-2.0 g / m²; The molar ratio of ruthenium, platinum, and neodymium in the ruthenium-based mixed oxide intermediate layer is (70-85):(5-15):(10-20), and the total metal loading is 5.0 g / m²-8.0 g / m². The molar ratio of platinum to cerium in the platinum-cerium mixed oxide protective layer is 30:70-40:60, and the total metal loading is 1.0 g / m²-3.0 g / m².
[0015] The method for preparing a multilayer composite oxide coating on a nickel substrate provided by this invention has the following beneficial effects: The synergistic effect of multiple components in the ruthenium-based mixed oxide intermediate layer, combined with the thin platinum transition layer to strengthen the interfacial bonding, enables the coating to maintain excellent chemical stability and interlayer bonding strength under harsh working conditions.
[0016] The in-situ generated nickel oxide underlayer is metallurgically bonded to the nickel substrate, significantly improving the bonding strength between the coating and the substrate and preventing coating peeling during long-term use; the doping of neodymium in the intermediate layer can stabilize the oxide lattice and inhibit the loss of coating components; the outer platinum-cerium mixed oxide is dense and continuous, which can effectively block the penetration of external corrosive media. The synergistic effect of the multi-layer structure extends the service life of the coated products.
[0017] The platinum-cerium mixed oxide outer layer can buffer the direct impact on the inner coating under the coupled impact of multiple factors, reduce irreversible structural damage to the intermediate layer, and improve the structural integrity of coated products under harsh working conditions.
[0018] All coatings are prepared using a wet chemical process of coating, drying, and thermal decomposition. The process parameters are easy to control, no complex preparation equipment is required, and it is suitable for large-scale industrial production. Attached Figure Description
[0019] Figure 1 This is a flowchart of a method for preparing a multilayer composite oxide coating on a nickel substrate surface provided in an embodiment of the present invention; Figure 2 This is a scanning electron microscope image of the surface morphology of the nickel-based multilayer composite coating product prepared in Example 1 of the present invention; Figure 3 This is a comparison chart of the overpotential test results of the embodiments and comparative examples of the present invention; Figure 4 This is a comparison chart of the remaining ruthenium content in the intermediate layer of each sample after 10 alternating forward and reverse current impact tests according to the present invention; The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0021] Reference Figure 1 This is a schematic flowchart of a method for preparing a multilayer composite oxide coating on a nickel substrate surface according to the present invention, including the following steps: S1, the surface of the nickel substrate is roughened by sandblasting, and then cleaned with organic solvent, immersed in acid solution and immersed in alkaline solution in sequence to obtain the pretreated nickel substrate; S2, the pretreated nickel substrate is placed in an oxygen-containing atmosphere for heating and heat preservation, and a nickel oxide underlayer is generated in situ on the surface of the nickel substrate; S3, a solution containing a platinum precursor is coated on the nickel oxide substrate, dried and then thermally decomposed. The coating, drying and thermal decomposition operations are repeated until a preset load is reached to form a thin platinum transition layer. S4, a mixed solution containing ruthenium precursor, platinum precursor and neodymium precursor is coated on the thin platinum transition layer, and after drying, it is subjected to thermal decomposition treatment. The coating, drying and thermal decomposition operations are repeated until a preset loading amount is reached to form a ruthenium-based mixed oxide intermediate layer. S5, a mixed solution containing platinum precursor and cerium precursor is coated on the intermediate layer of the ruthenium-based mixed oxide. After drying, it is subjected to thermal decomposition treatment. The coating, drying and thermal decomposition operations are repeated until a preset load is reached to form a platinum-cerium mixed oxide protective layer. S6, the nickel substrate with all coatings completed is placed in an oxygen-containing atmosphere for annealing treatment to obtain a multi-layer composite coated product of nickel substrate.
[0022] As described in step S1 above, a pure nickel mesh is selected as the nickel substrate and first undergoes sandblasting roughening treatment. 60-mesh corundum abrasive is used to sandblast the surface of the nickel mesh, creating a uniform rough microstructure with a surface roughness controlled within the range of Ra3.0-Ra10.0 μm. After sandblasting, surface dust is removed, and the nickel mesh is completely immersed in an acetone solution for ultrasonic cleaning to remove surface oil and organic impurities. The cleaning time is 30 minutes. After removal, it is transferred to anhydrous ethanol solution for further ultrasonic cleaning for 10 minutes to further purify the surface, followed by rinsing with pure water. The cleaned nickel mesh is then placed in a 20% sulfuric acid solution for ultrasonic treatment for 1 hour to fully dissolve and remove the naturally formed oxide film and sandblasting residue, exposing a fresh and dense metallic nickel surface. After treatment, the nickel mesh is removed and repeatedly rinsed with pure water until no residual acid remains on the surface. The nickel mesh is then placed in a 25% sodium hydroxide solution and ultrasonically treated for 20 minutes to neutralize any trace acidic residue on the surface and deeply remove any hidden oil and impurities. After removal, it is rinsed with pure water until the washing solution is neutral. The surface moisture is first allowed to air dry in a natural environment, and then it is placed in an oven at 50°C to dry, resulting in a clean pretreated nickel substrate with suitable roughness.
[0023] As described in step S2 above, the pretreated nickel substrate is fed into a muffle furnace. The furnace chamber is kept in an air atmosphere, and the temperature is steadily increased to 480-520℃ at a set rate. This temperature is maintained for 40-60 minutes. Under high temperature conditions, the metallic nickel on the surface of the nickel substrate undergoes a full oxidation reaction with the oxygen in the furnace, generating a continuous and uniform nickel oxide phase in situ on the substrate surface. The atmosphere remains stable throughout the holding process to ensure that the oxidation reaction proceeds fully and the surface oxidation degree is uniform and controllable, avoiding localized under-oxidation or over-oxidation. After the holding period, the heating power is cut off, and the nickel substrate cools naturally to room temperature with the furnace. The oxygen-containing atmosphere in the furnace is maintained throughout the process. The in-situ generated nickel oxide underlayer is metallurgically bonded to the nickel substrate, with high interfacial bonding strength. It is not prone to delamination or peeling during long-term service. The nickel oxide underlayer surface forms a suitable micro-rough structure, which can provide a reliable adhesion substrate for the coated thin platinum transition layer, while optimizing the interfacial bonding and structural compatibility between layers.
[0024] As described in step S3 above, chloroplatinic acid is dissolved in a solvent of isopropanol and deionized water at a volume ratio of 1:1. Hydrochloric acid solution is added dropwise to adjust the free hydrochloric acid concentration, preparing a platinum precursor solution with a total platinum concentration of 80-120 g / L. The prepared platinum precursor solution is then uniformly brushed onto the surface of the nickel oxide substrate, ensuring a consistent coating amount and complete coverage of the entire area to be treated, without any missed areas or localized accumulation. After coating, the nickel substrate is transferred to an oven and dried at 110-130°C for 5-15 minutes, allowing the solvent to slowly and fully evaporate, forming a smooth precursor film on the substrate surface. After drying, the substrate is transferred to a heating device with an oxygen-containing atmosphere and heated at 480-520°C for 15-25 minutes for thermal decomposition treatment, allowing the platinum precursor to fully decompose and transform, forming a strong interfacial bond with the underlying nickel oxide substrate. Repeat the above coating, drying and thermal decomposition operations 2-4 times until the platinum loading reaches 1.0-2.0 g / m², forming a thin platinum transition layer, which can enhance interlayer bonding and improve interface stability.
[0025] As described in step S4 above, ruthenium chloride, chloroplatinic acid, and neodymium nitrate are dissolved in a solvent containing isopropanol and deionized water in a 1:1 volume ratio at a ruthenium, platinum, and neodymium molar ratio of (70-85):(5-15):(10-20). The mixture is stirred until the solutes are completely dissolved, preparing a mixed coating solution with a mass concentration of 150-250 g / L based on the total metal content. The mixed coating solution is then uniformly brushed onto the surface of the thin platinum transition layer, ensuring a consistent coating amount per coat to guarantee the coating quality. The coating ensures complete coverage without any missed areas or localized liquid accumulation. After coating, the substrate is placed in an oven and dried at 100-140℃ for 5-15 minutes to allow the solvent to evaporate slowly, forming a uniform film layer on the substrate surface. After drying, the substrate is placed in an oxygen-containing heating device and held at 480-520℃ for 15-30 minutes for thermal decomposition treatment. This fully oxidizes the metal precursor into a mixed oxide, forming a strong interfacial bond with the underlying thin platinum transition layer. This brushing, drying, and thermal decomposition process is repeated 5-7 times until the total metal loading of the ruthenium-based mixed oxide intermediate layer reaches 5.0-8.0 g / m². The neodymium doping in the intermediate layer stabilizes the oxide lattice and inhibits the loss of coating components in harsh environments. The platinum and ruthenium-based oxides form a synergistic stabilizing effect, jointly ensuring the compactness and long-term service stability of the intermediate layer.
[0026] As described in step S5 above, chloroplatinic acid and cerium nitrate are dissolved in a solvent containing isopropanol and deionized water in a 1:1 volume ratio at a platinum to cerium molar ratio of 30:70 to 40:60. The mixture is stirred until the solute is completely dissolved, preparing a coating solution with a mass concentration of 80-120 g / L based on the total metal content. The coating solution is then uniformly brushed onto the surface of the ruthenium-based mixed oxide intermediate layer, ensuring uniform coating amount per coat to guarantee complete coverage of the area to be coated without any missed areas or localized liquid accumulation. After coating, the substrate is transferred to an oven and dried at 100-140°C for 5-15 minutes to allow the solvent to evaporate slowly, forming a uniform film layer of precursor on the surface of the intermediate layer. After drying, the substrate is placed in a heating device with an oxygen atmosphere and held at 430-490°C for 10-20 minutes for thermal decomposition treatment, allowing the metal precursor to be fully oxidized and converted into mixed oxide, forming a densely bonded interface with the underlying intermediate layer. Repeat the above brushing, drying and thermal decomposition operations 2-4 times until the total metal loading of the platinum-cerium mixed oxide protective layer reaches 1.0-3.0 g / m². This protective layer can block the direct erosion of the internal intermediate layer by external corrosive media, inhibit the loss of coating components, and buffer the direct effect on the internal structure during potential fluctuations or thermo-electric coupling shocks, reduce irreversible structural damage to the intermediate layer, and effectively improve the long-term service stability of the coated products.
[0027] As described in step S6 above, the nickel substrate, which sequentially forms a nickel oxide underlayer, a thin platinum transition layer, a ruthenium-based mixed oxide intermediate layer, and a platinum-cerium mixed oxide protective layer, is placed in a heating device containing an oxygen atmosphere and heated at a steady rate to 480-520°C. It is then held at this temperature for 20-40 minutes for annealing. During annealing, a stable air atmosphere is maintained in the furnace to fully release residual stress within each coating layer, while simultaneously promoting element diffusion and bonding at the interlayer interfaces. This further strengthens the interfacial bonding strength of the multilayer structure and improves the crystal phase structure of the oxides. After holding at this temperature, heating is stopped, and the nickel substrate cools naturally to room temperature with the furnace. The annealed multilayer composite coating product exhibits a dense and firm bond between each functional layer, reduced internal defects in the coating, and significantly improved overall structural stability. It can maintain long-term stable operation under high temperature, high humidity, and severe corrosion conditions, effectively extending the actual service life of the coated product.
[0028] The present invention will be specifically described below through examples and comparative examples.
[0029] Example 1 This embodiment prepares a nickel substrate multilayer composite coating product with a multilayer composite coating. A pure nickel mesh with a size of 5×5cm is selected as the substrate. The surface of the nickel mesh is roughened by sandblasting with 60-mesh corundum abrasive to achieve a surface roughness of Ra3-10μm. After removing the surface dust, the nickel mesh is completely immersed in acetone solution and ultrasonically cleaned for 30 minutes. After being taken out, it is transferred to anhydrous ethanol solution for further ultrasonic cleaning for 10 minutes, and then rinsed clean with deionized water.
[0030] The cleaned nickel mesh was ultrasonically treated in a 20% sulfuric acid solution for 1 hour to fully dissolve and remove the natural oxide film and residual dust from sandblasting, exposing a fresh metallic nickel surface. After removing the mesh, it was repeatedly rinsed with deionized water until no residual acid remained. Then, it was ultrasonically treated in a 25% sodium hydroxide solution for 20 minutes to neutralize any remaining acid and deeply remove trace amounts of oil. The mesh was then rinsed with deionized water until the washing solution was neutral, allowed to air dry, and then dried in a 50°C oven to obtain a pretreated nickel substrate. The pretreated nickel mesh was then placed in a muffle furnace under an air atmosphere and heat-treated to 500°C for 50 minutes to generate a continuous nickel oxide underlayer in situ on the mesh surface.
[0031] To prepare a platinum precursor coating solution, chloroplatinic acid was dissolved in a solvent of isopropanol and deionized water at a volume ratio of 1:1. Hydrochloric acid solution was added to adjust the free hydrochloric acid concentration to 0.1 mol / L, resulting in a coating solution with a total platinum concentration of 100 g / L. The coating solution was uniformly brushed onto the surface of a nickel oxide substrate and dried at 120°C for 10 minutes. Subsequently, it was placed in air and thermally decomposed at 500°C for 20 minutes. This brushing, drying, and thermal decomposition process was repeated three times until the platinum loading reached 1.5 g / m², forming a thin platinum transition layer.
[0032] A ruthenium-based mixed oxide intermediate coating solution was prepared by dissolving ruthenium chloride, chloroplatinic acid, and neodymium nitrate in a molar ratio of 85:5:10 (ruthenium, platinum, neodymium) in a solvent of isopropanol and deionized water in a volume ratio of 1:1. The solution was stirred until the solutes were completely dissolved, resulting in a total metal concentration of 200 g / L. The coating solution was then uniformly brushed onto the surface of a thin platinum transition layer and dried at 120°C for 10 minutes. Subsequently, it was thermally decomposed at 500°C in air for 20 minutes. This brushing, drying, and thermal decomposition process was repeated six times until the total metal loading of the intermediate layer reached 6.5 g / m², thus forming the ruthenium-based mixed oxide intermediate layer.
[0033] To prepare a platinum-cerium mixed oxide protective coating solution, chloroplatinic acid and cerium nitrate were dissolved in a solvent containing isopropanol and deionized water at a volume ratio of 1:1 (platinum:cerium molar ratio of 35:65). The solution was stirred until the solutes were completely dissolved, resulting in a total metal concentration of 100 g / L. The coating solution was then uniformly brushed onto the surface of the ruthenium-based mixed oxide intermediate layer and dried at 120°C for 10 minutes. Subsequently, it was thermally decomposed at 480°C in air for 10 minutes. This brushing, drying, and thermal decomposition process was repeated three times until the total metal loading of the protective layer reached 2.0 g / m², thus forming the platinum-cerium mixed oxide protective layer.
[0034] The nickel mesh with all coatings prepared was placed in a muffle furnace in an air atmosphere and annealed at 500°C for 30 minutes. After being naturally cooled to room temperature in the furnace, it was removed to obtain the finished product of multilayer composite coating on nickel substrate.
[0035] The surface morphology of the nickel-based multilayer composite coating product prepared in this embodiment was tested by scanning electron microscopy, and the results are as follows: Figure 2 As shown, under a 30μm observation scale, the multilayer coating on the surface of the coated product is observed to be continuous and dense, with oxide particles uniformly distributed on the substrate surface, without obvious cracks, peeling, or pinhole defects. After annealing, the functional layers are tightly bonded, and the surface platinum-cerium mixed oxide forms a complete and uniform coverage morphology, which can fully cover the underlying ruthenium-based intermediate layer. This not only preserves sufficient electrochemical reaction active sites but also provides a continuous physical barrier and potential buffer structure for the internal intermediate layer, consistent with the design effect of the multilayer coating of this invention.
[0036] Overpotential testing was performed on the nickel-based multilayer composite coating product prepared in this embodiment. The test system used a platinum sheet as the counter electrode and calomel as the reference electrode. The test solution was a 25% sodium hydroxide solution. Before testing, the product was stabilized by constant current operation at a current density of 1 kA / m² for 30 minutes, and the temperature of the test solution was controlled to be stable at 85±1℃. Subsequently, the current density was increased to 5.5 kA / m². After constant current operation for 60 minutes in the high current density conductive environment of 5.5 kA / m² until the potential stabilized, the overpotential for maintaining electrochemical stability was measured to be 68 mV, indicating that the multilayer coating structure is dense, the interlayer conductive channels are smooth, and there are no obvious high-impedance interface defects.
[0037] Example 2 This embodiment prepares a nickel substrate multilayer composite coating product with a multilayer composite coating. Except for the different precursor molar ratio of the ruthenium-based mixed oxide intermediate layer, the process parameters of substrate pretreatment, nickel oxide underlayer preparation, thin platinum transition layer preparation, platinum-cerium mixed oxide protective layer preparation and final annealing are completely consistent with those of Example 1.
[0038] To prepare the ruthenium-based mixed oxide intermediate coating solution, ruthenium chloride, chloroplatinic acid, and neodymium nitrate were dissolved in a solvent containing isopropanol and deionized water in a volume ratio of 80:10:10 (ruthenium, platinum, neodymium molar ratio). The solution was stirred until the solutes were completely dissolved, resulting in a coating solution with a total metal concentration of 200 g / L. The coating solution was then uniformly brushed onto the surface of a thin platinum transition layer and dried at 120°C for 10 minutes. Subsequently, it was thermally decomposed at 500°C in air for 20 minutes. This brushing, drying, and thermal decomposition process was repeated six times until the total metal loading of the intermediate layer reached 6.5 g / m², thus forming the ruthenium-based mixed oxide intermediate layer.
[0039] The nickel-based multilayer composite coating product prepared in this example was subjected to overpotential testing under the same test conditions as in Example 1. After the potential stabilized in a 25% sodium hydroxide solution with a current density of 5.5 kA / m² and a temperature of 85°C, the overpotential was measured to be 71 mV.
[0040] Example 3 This embodiment prepares a nickel substrate multilayer composite coating product with a multilayer composite coating. Except for the different precursor molar ratio of the ruthenium-based mixed oxide intermediate layer, the process parameters of substrate pretreatment, nickel oxide underlayer preparation, thin platinum transition layer preparation, platinum-cerium mixed oxide protective layer preparation and final annealing are completely consistent with those of Example 1.
[0041] To prepare the ruthenium-based mixed oxide intermediate coating solution, ruthenium chloride, chloroplatinic acid, and neodymium nitrate were dissolved in a solvent containing isopropanol and deionized water in a 1:1 volume ratio (ruthenium, platinum, neodymium molar ratio of 75:10:15). The solution was stirred until the solutes were completely dissolved, resulting in a coating solution with a total metal concentration of 200 g / L. The coating solution was then uniformly brushed onto the surface of a thin platinum transition layer and dried at 120°C for 10 minutes. Subsequently, it was thermally decomposed at 500°C for 20 minutes in air. This brushing, drying, and thermal decomposition process was repeated six times until the total metal loading of the intermediate layer reached 6.5 g / m², thus forming the ruthenium-based mixed oxide intermediate layer.
[0042] The nickel-based multilayer composite coating product prepared in this example was subjected to overpotential testing under the same test conditions as in Example 1. The overpotential was measured to be 79mV after the potential stabilized in a 25% sodium hydroxide solution at a current density of 5.5kA / m² and a temperature of 85°C.
[0043] Example 4 This embodiment prepares a nickel substrate multilayer composite coating product with a multilayer composite coating. Except for the different precursor molar ratio of the ruthenium-based mixed oxide intermediate layer, the process parameters of substrate pretreatment, nickel oxide underlayer preparation, thin platinum transition layer preparation, platinum-cerium mixed oxide protective layer preparation and final annealing are completely consistent with those of Example 1.
[0044] To prepare the ruthenium-based mixed oxide intermediate coating solution, ruthenium chloride, chloroplatinic acid, and neodymium nitrate were dissolved in a solvent containing isopropanol and deionized water in a 1:1 volume ratio (ruthenium, platinum, neodymium molar ratio) at a ratio of 75:5:20. The solution was stirred until the solutes were completely dissolved, resulting in a coating solution with a total metal concentration of 200 g / L. The coating solution was then uniformly brushed onto the surface of a thin platinum transition layer and dried at 120°C for 10 minutes. Subsequently, it was thermally decomposed at 500°C in air for 20 minutes. This brushing, drying, and thermal decomposition process was repeated six times until the total metal loading of the intermediate layer reached 6.5 g / m², thus forming the ruthenium-based mixed oxide intermediate layer.
[0045] The nickel-based multilayer composite coating product prepared in this example was subjected to overpotential testing under the same test conditions as in Example 1. After the potential stabilized in a 25% sodium hydroxide solution with a current density of 5.5 kA / m² and a temperature of 85°C, the overpotential was measured to be 81 mV.
[0046] Example 5 This embodiment prepares a nickel substrate multilayer composite coating product with a multilayer composite coating. Except for the different precursor molar ratio of the ruthenium-based mixed oxide intermediate layer, the process parameters of substrate pretreatment, nickel oxide underlayer preparation, thin platinum transition layer preparation, platinum-cerium mixed oxide protective layer preparation and final annealing are completely consistent with those of Example 1.
[0047] To prepare the ruthenium-based mixed oxide intermediate coating solution, ruthenium chloride, chloroplatinic acid, and neodymium nitrate were dissolved in a solvent containing isopropanol and deionized water in a 1:1 volume ratio (ruthenium, platinum, neodymium molar ratio) at a ratio of 70:15:15. The solution was stirred until the solutes were completely dissolved, resulting in a coating solution with a total metal concentration of 200 g / L. The coating solution was then uniformly brushed onto the surface of a thin platinum transition layer and dried at 120°C for 10 minutes. Subsequently, it was thermally decomposed at 500°C in air for 20 minutes. This brushing, drying, and thermal decomposition process was repeated six times until the total metal loading of the intermediate layer reached 6.5 g / m², thus forming the ruthenium-based mixed oxide intermediate layer.
[0048] The nickel-based multilayer composite coating product prepared in this example was subjected to overpotential testing under the same test conditions as in Example 1. The overpotential was measured to be 74mV after the potential stabilized in a 25% sodium hydroxide solution at a current density of 5.5kA / m² and a temperature of 85°C.
[0049] Comparative Example 1 This comparative example prepares a multilayer composite coating product on a nickel substrate. Except for omitting the preparation step of the nickel oxide underlayer, the process parameters for substrate pretreatment, thin platinum transition layer preparation, ruthenium-based mixed oxide intermediate layer preparation, platinum-cerium mixed oxide protective layer preparation, and final annealing are completely consistent with those in Example 1. The pretreated nickel mesh is not subjected to high-temperature oxidation treatment; instead, a platinum precursor coating solution is directly brushed onto the clean metallic nickel surface to prepare the thin platinum transition layer.
[0050] The nickel-based multilayer composite coating product prepared in this comparative example was subjected to overpotential testing under the same test conditions as in Example 1. After the potential stabilized in a 25% sodium hydroxide solution with a current density of 5.5 kA / m² and a temperature of 85°C, the overpotential was measured to be 72 mV.
[0051] The results of this comparative example demonstrate that the nickel oxide underlayer not only acts as a physical bonding layer to improve the adhesion between the coating and the substrate, but also makes a significant contribution to electronic conduction and the stability of the overall structure. Without this layer, the adhesion between the coating and the substrate is insufficient, making it prone to peeling failure under long-term conductive service and potential fluctuations.
[0052] Comparative Example 2 This comparative example prepares a multilayer composite coating product on a nickel substrate. Except for omitting the preparation step of the thin platinum transition layer, the process parameters for substrate pretreatment, nickel oxide underlayer preparation, ruthenium-based mixed oxide intermediate layer preparation, platinum-cerium mixed oxide protective layer preparation, and final annealing are completely consistent with those in Example 1. The nickel mesh with the completed nickel oxide underlayer is not subjected to platinum precursor coating and thermal decomposition treatment; instead, a ruthenium-based mixed oxide intermediate layer coating solution is directly brushed onto the surface of the nickel oxide underlayer to prepare the intermediate layer.
[0053] The nickel-based multilayer composite coating product prepared in this comparative example was subjected to overpotential testing under the same test conditions as in Example 1. After the potential stabilized in a 25% sodium hydroxide solution with a current density of 5.5 kA / m² and a temperature of 85°C, the overpotential was measured to be 93 mV.
[0054] The results of this comparative example show that the thin platinum layer plays an irreplaceable role in electron conduction and interlayer charge transfer. Without this layer, the interfacial resistance between the nickel oxide substrate and the ruthenium-based intermediate layer increases significantly, and the bonding force between the intermediate layer and the substrate also decreases due to the lack of a transition layer.
[0055] Comparative Example 3 This comparative example prepares a multilayer composite coated product on a nickel substrate. Except for omitting the preparation step of the platinum-cerium mixed oxide protective layer, the process parameters for substrate pretreatment, nickel oxide underlayer preparation, thin platinum transition layer preparation, ruthenium-based mixed oxide intermediate layer preparation, and final annealing are completely consistent with those in Example 1. The nickel mesh after completing the ruthenium-based mixed oxide intermediate layer preparation is directly subjected to the final annealing process without undergoing protective layer coating and thermal decomposition treatment.
[0056] The nickel-based multilayer composite coating product prepared in this comparative example was subjected to overpotential testing under the same test conditions as in Example 1. The overpotential was measured to be 70mV after the potential stabilized in a 25% sodium hydroxide solution at a current density of 5.5kA / m² and a temperature of 85°C.
[0057] The results of this comparative example indicate that the primary function of the platinum-cerium protective layer is not to enhance initial activity, but rather to protect the underlying intermediate layer from contamination by impurities in the test solution and damage from potential fluctuations. Without this layer, the long-term stability and resistance to backflow of the coated product are significantly compromised.
[0058] Comparative Example 4 This comparative example prepares a multilayer composite coating product on a nickel substrate. Except for omitting the preparation process of the platinum-cerium mixed oxide protective layer and replacing the ruthenium-based mixed oxide intermediate layer with a pure ruthenium oxide intermediate layer (using only ruthenium chloride as a precursor, without adding chloroplatinic acid and neodymium nitrate), the process parameters for the remaining substrate pretreatment, nickel oxide underlayer preparation, thin platinum transition layer preparation, and final annealing treatment are completely consistent with those in Example 1.
[0059] When preparing the intermediate coating solution, ruthenium chloride was dissolved in a solvent consisting of isopropanol and deionized water in a 1:1 volume ratio. The solution was stirred until the solute was completely dissolved, resulting in a total metal concentration of 200 g / L. The coating solution was then uniformly brushed onto the surface of a thin platinum transition layer and dried at 120°C for 10 minutes. Subsequently, it was placed in air and thermally decomposed at 500°C for 20 minutes. This brushing, drying, and thermal decomposition process was repeated six times until the total metal loading of the intermediate layer reached 6.5 g / m², forming a pure ruthenium oxide intermediate layer.
[0060] The nickel-based multilayer composite coating product prepared in this comparative example was subjected to overpotential testing under the same test conditions as in Example 1. After the potential stabilized in a 25% sodium hydroxide solution with a current density of 5.5 kA / m² and a temperature of 85°C, the overpotential was measured to be 101 mV.
[0061] The results of this comparative example show that although the pure ruthenium oxide interlayer possesses certain intrinsic activity, its stability is severely insufficient under harsh conductive environments. The rapid dissolution and detachment of ruthenium completely fails to meet the requirements for long-term operation. The addition of small amounts of platinum and neodymium plays a crucial role in stabilizing the ruthenium oxide structure and extending the lifespan of the coated products.
[0062] Comparative Example 5 This comparative example prepares a multilayer composite coating product on a nickel substrate. Except for replacing the platinum-cerium mixed oxide protective layer with a pure cerium dioxide protective layer, using only cerium nitrate as a precursor and not adding chloroplatinic acid, the process parameters for the substrate pretreatment, nickel oxide underlayer preparation, thin platinum transition layer preparation, ruthenium-based mixed oxide intermediate layer preparation, and final annealing treatment are completely consistent with those in Example 1.
[0063] When preparing the protective coating solution, cerium nitrate was dissolved in a solvent containing isopropanol and deionized water at a volume ratio of 1:1, and stirred until the solute was completely dissolved, resulting in a coating solution with a total metal concentration of 100 g / L. The coating solution was then uniformly brushed onto the surface of the ruthenium-based mixed oxide intermediate layer and dried at 120°C for 10 minutes, followed by thermal decomposition at 480°C in air for 10 minutes. This brushing, drying, and thermal decomposition process was repeated three times until the total metal loading of the protective layer reached 2.0 g / m², forming a pure cerium dioxide protective layer.
[0064] The nickel-based multilayer composite coating product prepared in this comparative example was subjected to overpotential testing under the same test conditions as in Example 1. After the potential stabilized in a 25% sodium hydroxide solution with a current density of 5.5 kA / m² and a temperature of 85°C, the overpotential was measured to be 76 mV.
[0065] The results of this comparative example show that when the protective layer does not contain platinum, the conductivity of the protective layer itself is insufficient, which increases the interfacial resistance and leads to an increase in overpotential. At the same time, the density and structural stability of cerium dioxide are not as good as those of the platinum-cerium mixed oxide, and the anti-reverse current protection effect is weakened.
[0066] The overpotential test results for each sample are as follows: Figure 3 As shown, the overpotentials of Examples 1 to 5 are in the range of 68mV to 81mV, all exhibiting excellent conductivity stability. Among them, Example 1, corresponding to an intermediate layer ratio of 85:5:10 for ruthenium, platinum, and neodymium, has the lowest overpotential and the best catalytic activity. With the increase of neodymium doping ratio and the adjustment of platinum ratio, the overpotential shows a slight upward trend. An appropriate platinum-neodymium doping ratio can maintain high catalytic activity while ensuring structural stability.
[0067] Comparative Example 1, lacking a nickel oxide underlayer, had an overpotential of 72 mV, close to that of Example 1. The nickel oxide underlayer has little impact on the initial catalytic activity of the coated product; its core function is to enhance the bonding strength between the coating and the substrate, ensuring structural stability during long-term operation. Comparative Example 2, lacking a thin platinum transition layer, had an overpotential of 93 mV and a significantly increased interfacial resistance, verifying the crucial role of the thin platinum transition layer in reducing interlayer charge transfer resistance and optimizing electron conduction pathways. Comparative Example 3, lacking a platinum-cerium mixed oxide protective layer, had an overpotential of 70 mV, with no significant decrease in initial activity. The protective layer does not directly contribute to catalytic activity; its core function lies in long-term protection and reverse current tolerance. Comparative Example 4, using a pure ruthenium oxide interlayer, had an overpotential as high as 101 mV, resulting in a significant decrease in catalytic activity, demonstrating that platinum and neodymium co-doping can effectively optimize the electronic structure of the interlayer and improve electrochemical reaction kinetics. Comparative Example 5, using a pure cerium dioxide protective layer, had an overpotential of 76 mV, slightly higher than the Example group, due to the increased interfacial resistance caused by the insufficient conductivity of pure cerium oxide.
[0068] The prepared nickel-based multilayer composite coating was subjected to a 6-hour operation in a 25% NaOH solution at 85±1℃ under a forward constant current of 5.5 kA / m². Subsequently, a reverse current (100 A / m²) was applied for 2 hours, and this cycle was repeated 10 times to simulate the structural stability of the coating under conditions of drastic potential fluctuations and electro-thermal coupling shock. After the test, X-ray fluorescence spectroscopy (XRF) was used to analyze the remaining mass of ruthenium in the intermediate layer, and the residual rate was calculated by comparing it with the initial loading. The results are as follows: Figure 4 As shown.
[0069] The residual ruthenium content of all sample examples remained in the range of 81.3% to 84.2%, significantly higher than that of the comparative samples. This indicates that the multilayer composite coating structure proposed in this invention can effectively buffer reverse current impacts and suppress the dissolution and loss of ruthenium during potential fluctuations, demonstrating excellent operating condition tolerance. Example 1 showed the highest residual ruthenium content at 84.2%, corresponding to a molar ratio of 85:5:10 for the intermediate layer of ruthenium, platinum, and neodymium, achieving optimal balance between catalytic activity and structural stability. Examples 2 and 5 showed residual ruthenium contents of 83.5% and 83.6%, respectively, also at a high level, verifying that appropriate platinum and neodymium co-doping can effectively stabilize the oxide lattice and mitigate the drastic valence state changes and structural damage of ruthenium under reverse current. In Examples 3 and 4, the residual ruthenium content decreased slightly with adjustments to the doping ratio, but remained above 81%, exhibiting excellent overall stability.
[0070] Comparative Example 1, lacking the in-situ nickel oxide underlayer, had a remaining ruthenium content of 71.5%, a significant decrease compared to the Example Group. The nickel oxide underlayer is metallurgically bonded to the nickel substrate and forms the basis for the overall coating structure. Without this layer, repeated reverse current impacts easily cause the coating interface to loosen and generate microcracks. The test solution penetrates along the interface, accelerating the dissolution of ruthenium, demonstrating that the nickel oxide underlayer plays an indispensable supporting role in stabilizing the overall coating structure.
[0071] Comparative Example 2, lacking the thin platinum transition layer, had a remaining ruthenium content of 68%, resulting in a further significant performance degradation. The thin platinum transition layer optimizes interlayer charge transport and matches the interlayer thermal expansion coefficient. The absence of this layer leads to increased interlayer interface resistance, uneven interlayer potential distribution under reverse current, and excessively high local overpotentials that exacerbate ruthenium oxidation and dissolution. Simultaneously, decreased interlayer bonding strength also accelerates coating structural failure.
[0072] In Comparative Example 3, lacking the platinum-cerium mixed oxide protective layer, the remaining ruthenium content was only 56.4%, a significant decrease. The outer protective layer is the first barrier against reverse current impact. Without it, the reverse current directly acts on the inner ruthenium-based intermediate layer, causing irreversible oxidation and significant loss of ruthenium on the surface of the intermediate layer. This directly verifies the core role of the platinum-cerium mixed oxide protective layer in buffering reverse current and shielding against test solution corrosion.
[0073] Comparative Example 4 used a pure ruthenium oxide interlayer without platinum or neodymium doping, resulting in a ruthenium content of only 35.3%, the lowest among all samples. The crystal structure of pure ruthenium oxide is easily disrupted under the oxidative stress of a reverse current, leading to rapid dissolution of high-valence ruthenium. This clearly demonstrates that co-doping with platinum and neodymium effectively anchors the oxide lattice, enhancing the structural stability of the interlayer under potential fluctuations, and is the core intrinsic factor in suppressing ruthenium dissolution and loss.
[0074] Comparative Example 5 used a pure cerium dioxide protective layer without adding platinum components, and the remaining ruthenium content was 64.8%. Its protective effect was weaker than that of the Example Group, but better than that of Comparative Example 3 without a protective layer. Pure cerium dioxide can play a certain physical barrier role, but its own conductivity is insufficient, and it cannot uniformly disperse the potential impact under reverse current, thus limiting its protective capability. This verifies that the protective layer constructed by platinum and cerium can balance conductivity and barrier performance, achieving a better reverse current protection effect.
[0075] In summary, the multilayer composite coating structure of the present invention forms a synergistic effect from multiple dimensions such as interface bonding enhancement, lattice stabilization doping, and outer layer buffer protection. Each layer plays a key role in improving the structural stability of the coated product and inhibiting the loss of coating components. The multilayer structure together ensures the long service life of the coated product under harsh conditions such as high temperature, high humidity, and potential fluctuations.
[0076] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, apparatus, article, or method that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, apparatus, article, or method. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, apparatus, article, or method that includes that element.
[0077] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A method for preparing a multilayer composite oxide coating on a nickel substrate surface, comprising the steps of nickel substrate pretreatment, precursor coating, and thermal decomposition to prepare the coating, characterized in that, Includes the following steps: The surface of the nickel substrate is roughened by sandblasting, and then cleaned with organic solvent, immersed in acid solution and immersed in alkaline solution in sequence to obtain the pretreated nickel substrate. The pretreated nickel substrate is heated and kept warm in an oxygen-containing atmosphere to generate an in-situ nickel oxide underlayer on the surface of the nickel substrate. A solution containing a platinum precursor is coated onto the nickel oxide substrate, dried, and then thermally decomposed. The coating, drying, and thermal decomposition processes are repeated until a preset loading amount is reached to form a thin platinum transition layer. A mixed solution containing ruthenium precursor, platinum precursor and neodymium precursor is coated on the thin platinum transition layer. After drying, it is subjected to thermal decomposition treatment. The coating, drying and thermal decomposition operations are repeated until a preset loading amount is reached to form a ruthenium-based mixed oxide intermediate layer. A mixed solution containing platinum precursor and cerium precursor is coated on the intermediate layer of the ruthenium-based mixed oxide. After drying, it is subjected to thermal decomposition treatment. The coating, drying and thermal decomposition operations are repeated until a preset load is reached to form a platinum-cerium mixed oxide protective layer. The nickel substrate with all coatings completed is placed in an oxygen-containing atmosphere for annealing to obtain a multilayer composite coated nickel substrate.
2. The method for preparing a multilayer composite oxide coating on a nickel substrate surface according to claim 1, characterized in that, The step of coating a platinum-containing precursor solution onto the nickel oxide substrate, drying it, and then thermally decomposing it, repeating the coating, drying, and thermal decomposition process until a preset loading amount is reached to form a thin platinum transition layer, includes: Chloroplatinic acid was dissolved in a solvent in which isopropanol and deionized water were mixed in a volume ratio of 1:
1. Hydrochloric acid solution was added to adjust the acidity, and a platinum precursor solution with a total platinum concentration of 80-120 g / L was prepared. The platinum precursor solution is uniformly coated on the surface of the nickel oxide substrate and dried at 110℃-130℃ for 5-15 minutes, allowing the solvent to slowly evaporate and forming a precursor film on the substrate surface. The dried substrate is placed in an oxygen-containing atmosphere and kept at 480℃-520℃ for 15-25 minutes for thermal decomposition treatment, so that the platinum precursor is fully decomposed and transformed, and forms an interface bond with the underlying nickel oxide substrate. Repeat the above coating, drying and thermal decomposition operations 2-4 times until the platinum loading reaches 1.0-2.0 g / m², forming a continuous thin platinum transition layer.
3. The method for preparing a multilayer composite oxide coating on a nickel substrate surface according to claim 2, characterized in that, The step of dissolving chloroplatinic acid in a solvent of isopropanol and deionized water in a 1:1 volume ratio, adjusting the acidity with hydrochloric acid solution, and preparing a platinum precursor solution with a total platinum concentration of 80-120 g / L includes: Add chloroplatinic acid to a solvent in which isopropanol and deionized water are mixed in a volume ratio of 1:1, and stir until completely dissolved; Hydrochloric acid solution was added dropwise while stirring to adjust the acidity of the solution to a concentration of 0.05 mol / L to 0.2 mol / L. Stirring was continued until the solution became clear and transparent to obtain the platinum precursor solution.
4. The method for preparing a multilayer composite oxide coating on a nickel substrate surface according to claim 1, characterized in that, The step of coating a mixed solution containing ruthenium precursor, platinum precursor and neodymium precursor onto the thin platinum transition layer, drying it and then thermally decomposing it, repeating the coating, drying and thermal decomposition operations until a preset loading amount is reached to form a ruthenium-based mixed oxide intermediate layer includes: Ruthenium chloride, chloroplatinic acid, and neodymium nitrate are dissolved in a mixed solvent of isopropanol and deionized water at a molar ratio of ruthenium, platinum, and neodymium of (70-85):(5-15):(10-20) to prepare a coating solution. The mass concentration of the coating solution, based on the total metal content, is 150 g / L-250 g / L. The coating liquid is brushed onto the surface of the thin platinum transition layer, dried at 100℃-140℃ for 5-15 minutes, and then thermally decomposed at 480℃-520℃ in an oxygen-containing atmosphere for 15-30 minutes. Repeat the brushing, drying and thermal decomposition process 5 to 7 times until the total metal loading in the ruthenium-based mixed oxide intermediate layer reaches 5.0 g / m² to 8.0 g / m².
5. The method for preparing a multilayer composite oxide coating on a nickel substrate surface according to claim 1, characterized in that, The step of coating a mixed solution containing platinum and cerium precursors onto the ruthenium-based mixed oxide intermediate layer, drying it, and then subjecting it to thermal decomposition, repeating the coating, drying, and thermal decomposition operations until a preset loading amount is reached to form a platinum-cerium mixed oxide protective layer, includes: Chloroplatinic acid and cerium nitrate were dissolved in a mixed solvent of isopropanol and deionized water at a platinum to cerium molar ratio of 30:70-40:60 to prepare a coating solution. The mass concentration of the coating solution, based on the total metal content, was 80 g / L-120 g / L. The coating solution is brushed onto the surface of the ruthenium-based mixed oxide intermediate layer and dried at 100℃-140℃ for 5-15 minutes, followed by thermal decomposition at 430℃-490℃ in an oxygen-containing atmosphere for 10-20 minutes. Repeat the brushing, drying, and thermal decomposition process 2 to 4 times until the total metal loading of the protective layer reaches 1.0 g / m² to 3.0 g / m², forming a continuous platinum-cerium mixed oxide protective layer.
6. The method for preparing a multilayer composite oxide coating on a nickel substrate surface according to claim 1, characterized in that, The step of placing the pretreated nickel substrate in an oxygen-containing atmosphere for heating and heat preservation to generate an in-situ nickel oxide underlayer on the surface of the nickel substrate includes: The pretreated nickel substrate is placed in an oxygen-containing atmosphere and heated to 480℃-520℃ and held for 40-60 minutes. After the heat preservation is completed, heating is stopped, and the nickel substrate cools with the furnace, forming a continuous nickel oxide underlayer that is metallurgically bonded to the substrate on the surface.
7. The method for preparing a multilayer composite oxide coating on a nickel substrate surface according to claim 1, characterized in that, The step of annealing the nickel substrate with all coatings completed in an oxygen-containing atmosphere to obtain a multilayer composite coated nickel substrate includes: A nickel substrate having a nickel oxide underlayer, a thin platinum transition layer, a ruthenium-based mixed oxide intermediate layer and a platinum-cerium mixed oxide protective layer formed sequentially is placed in an oxygen-containing atmosphere and heated to 480℃-520℃ and held for 20-40 minutes. After the heat preservation is completed, heating is stopped, and the nickel substrate is cooled with the furnace to eliminate internal stress in the coating and stabilize the interfacial bonding between the coatings, thus obtaining a multi-layer composite coating product with a nickel substrate.
8. A multilayer composite coating product on a nickel substrate surface, characterized in that, It is prepared by the method for preparing a multilayer composite oxide coating on a nickel substrate surface according to any one of claims 1 to 7.
9. The multilayer composite coating product on a nickel substrate surface according to claim 8, characterized in that, The substrate includes a nickel substrate, the surface of which is provided with, from the inside out, a nickel oxide underlayer, a thin platinum transition layer, a ruthenium-based mixed oxide intermediate layer, and a platinum-cerium mixed oxide protective layer. The platinum loading of the thin platinum transition layer is 1.0 g / m²-2.0 g / m²; The molar ratio of ruthenium, platinum, and neodymium in the ruthenium-based mixed oxide intermediate layer is (70-85):(5-15):(10-20), and the total metal loading is 5.0 g / m²-8.0 g / m². The molar ratio of platinum to cerium in the platinum-cerium mixed oxide protective layer is 30:70-40:60, and the total metal loading is 1.0 g / m²-3.0 g / m².
Citation Information
Patent Citations
Method for preparing composite active cathode
CN102321892A
Electrode base, negative electrode for aqueous solution electrolysis using same, method for producing the electrode base, and method for producing the negative electrode for aqueous solution electrolysis
CN102770587A